La ciencia jurídica positiva y el jusnaturalismo - Gioja, Ambrosio L. (2008)
"Originally published in Revista Jurídica de Buenos Aires, no. IV, Buenos Aires, Department of Publications, Faculty of Law and Social Sciences, University of Buenos Aires, 1961, pp. 95-117"